ASSOCIATION BETWEEN WELL WATER QUALITY AND DIARRHEA INCIDENCE AROUND PAKUSARI FINAL DISPOSAL SITE JEMBER INDONESIA - Elvinsyah Zidane; Isa Ma’rufi; Ristya Widi Endah Yani (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2026)
Well water quality in communities surrounding final disposal sites is susceptible to deterioration because of leachate contamination, increasing the risk of diarrheal disease. The objective was to analyze the association between well water quality and diarrhea incidence among communities living around the Pakusari Final Disposal Site, Jember, Indonesia. A quantitative observational study with a cross-sectional design was conducted involving 20 households using well water and six representative well water samples collected through the grab sampling method. Data were obtained through structured interviews, field observations, and laboratory analyses of physical, chemical, and microbiological water parameters. Escherichia coli contamination was determined using the Most Probable Number (MPN) method. Data were analyzed using descriptive statistics, the Chi-square test, and logistic regression. Results showed that all well water samples (100%) were contaminated with Escherichia coli and failed to comply with microbiological drinking water standards under the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023. Diarrhea occurred in 55.0% of respondents. Physical and chemical parameters were not significantly associated with diarrhea incidence (p > 0.05), whereas boiling drinking water was significantly associated (p = 0.038). Poor microbiological water quality and household water treatment practices contributed to diarrhea incidence.